PERGERAKAN HARGA SAHAM SEKTOR PROPERTI BURSA EFEK JAKARTA BERDASARKAN KONDISI PROFITABILITAS, SUKU BUNGA DAN BETA SAHAM - Suhardi, Deddy A. (Jurnal Organisasi dan Manajemen, 2007)
Understanding the empirical description of stock prices movement on the economical setting, firm?s perform, and the behavior of its beta is fundamental to portfolio risk management. This study evaluates the effect of three factors: firm?s profitability, interest rate, and beta, toward the stock prices movement of 32 property stocks listing at Jakarta Stock Exchange (BEJ). Path analytical model was designed with interest and return on asset (ROA) profitability as the exogenous, stock beta became an intervening variable and average rate of stock prices movement became an endogenous variable. Daily prices for the stocks, BEJ Composite Index, profitability, and interest rate were obtained from BEJ and Bank Indonesia tapes for January 2000 to December 2004 period. This analysis indicated that the stock prices movement was the most dominant influenced by beta followed by interest rate (negative) and firm?s profitability. This study also found that beta would become an effective intervening variable for transmitting both ROA and interest effect toward the stock prices movements, and hence the role of beta could be adopted as investor strategy. Structurally, the average rate of stocks prices movement would be up about: 0.37 standard units if beta was force up about one standard unit (of increasing on ROA or decreasing on interest or both together), 0.24 standard units if interest rate was lead to set down about one standard unit of ceteris paribus, and 0.19 standard units if ROA was grow about one standard unit of ceteris paribus. Furthermore, the stock prices movement of BEJ property stocks by forcing of the investor strategy was higher than leading the economical setting which it was higher than its firm?s fundamental perform growing.